Synthesis of ω-amino-α-phenylcarbonate alkanes and their polymerization to [n]-polyurethanes - Arce, Silvina M. (2010)
Aliphatic [n]-polyurethanes have recently been synthesized from ω-isocyanato-α-alkanols or, more traditionally, by cationic ring-opening polymerization of cyclourethanes or by the Bu2Sn(OMe)2-promoted polycondensation of ω-hydroxy-α-O- phenylurethane alkanes. For the latter procedures, the conditions employed do not seem to be suitable for highly functionalized monomers. In contrast, the polymerization of ω-amino-α-phenylcarbonate alkanes is expected to occur under milder conditions. ω-Amino-α-phenylcarbonate alkanes have been synthesized from 6-aminohexanol (1) and 3-aminopropanol (6). The procedure involves the N-Boc protection of the amino group, followed by activation of the alcohol. Removal of the N-Boc affords the corresponding ω-amino-1-O-phenyloxycarbonyloxyalkane hydrochlorides. Other oligomeric comonomers between 1 and 6 have been prepared. The polymerization of these precursors takes place in the absence of metal catalysts to afford the corresponding linear and regioregular [n]-polyurethanes. The procedure described is useful for the preparation of stable ω-amino-α-phenylcarbonate alkane derivatives, which possess varied chain lengths between the terminal functions. These monomers yield [n]-polyurethanes having various structures starting from just two aminoalkanols. The polyurethanes were obtained in high yields, with reasonable molecular weight and polydispersity values, and they were characterized spectroscopically and thermally. These studies reveal constitutionally uniform structures that are free of carbonate or urea linkages.